Blood n-3 fatty acid levels and total and cause-specific mortality from 17 prospective studies - Harris, William S.; Tintle, Nathan L.; Imamura, Fumiaki; Qian, Frank; Korat, Andres V. Ardisson; Marklund, Matti; Djoussé, Luc; Bassett, Julie K.; Carmichael, Pierre-Hugues; Chen, Yun-Yu; Hirakawa, Yoichiro; Küpers, Leanne K.; et al. (Nature communications, 2021)
The health effects of omega-3 fatty acids have been controversial. Here we report the results of a de novo pooled analysis conducted with data from 17 prospective cohort studies examining the associations between blood omega-3 fatty acid levels and risk for all-cause mortality. Over a median of 16 years of follow-up, 15,720 deaths occurred among 42,466 individuals. We found that, after multivariable adjustment for relevant risk factors, risk for death from all causes was significantly lower (by 15–18%, at least p < 0.003) in the highest vs the lowest quintile for circulating long chain (20–22 carbon) omega-3 fatty acids (eicosapentaenoic, docosapentaenoic, and docosahexaenoic acids). Similar relationships were seen for death from cardiovascular disease, cancer and other causes. No associations were seen with the 18-carbon omega-3, alpha-linolenic acid. These findings suggest that higher circulating levels of marine n-3 PUFA are associated with a lower risk of premature death. Associations between of omega-3 fatty acids and mortality are not clear. Here the authors report that, based on a pooled analysis of 17 prospective cohort studies, higher blood omega-3 fatty acid levels correlate with lower risk of all-cause mortality.